Electrochemical device and electronic device

By using a barrier in the electrochemical device to separate the electrode component from the electrolyte, and connect the connection through the polar ear, the existing lithium -ion battery has a short -circuit problem in the electrolyte decomposition of the electrolyte and in the electrode component during the high voltage output. The effect of voltage output and lowering heating.

CN119340451APending Publication Date: 2025-01-21NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411530435.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2020-06-30
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have problems with electrolyte decomposition and short circuit in electrode assembly when outputting high voltage, resulting in battery failure and difficult to promote to mainstream liquid electrolyte batteries.

Method used

A electrochemical device is designed to separate the electrode component and the electrolyte into an independent cavity with a partition, and connect it through the polar ear series. The barrier has an ion insulating layer to avoid electrolyte high -voltage decomposition and short circuit in the electrode component.

Benefits of technology

The high voltage output is achieved, while the temperature of the electrochemical device is reduced, the water resistance and environmental stability of the battery are improved, and the risk of battery failure is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340451A_ABST
    Figure CN119340451A_ABST
Patent Text Reader

Abstract

An electrochemical device comprises a partition plate, the partition plate is connected with an outer package in a sealed mode, independent cavities are formed in the two sides of the partition plate respectively, each cavity comprises an electrode assembly and electrolyte, the electrode assemblies in the adjacent cavities are connected in series through tabs, the partition plate comprises an ion insulation layer, and the ion insulation layer is arranged on the outer package. The water permeability of the partition plate is less than or equal to 10 <-3 > g / (day.m < 2 >. Pa) / 3mm; and the seal thickness T and the seal width W for sealing the partition plate and the outer package meet the condition that T / W is greater than or equal to 0.01 and less than or equal to 0.05. According to the electrochemical device, high-voltage output can be realized, the temperature rise amplitude of the electrochemical device is reduced, and the water resistance and environmental stability of the electrochemical device can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese patent application submitted to the China Patent Office on June 30, 2020, with application number 202080053282.5 and invention name “An electrochemical device and electronic device”. Technical Field

[0002] The present invention relates to the field of electrochemistry, and in particular to an electrochemical device and an electronic device using the electrochemical device. Background Art

[0003] In the existing lithium-ion battery system, due to the limited voltage difference between the positive and negative electrode materials and the limited anti-oxidation and reduction capacity of the electrolyte, the open circuit voltage of the battery is difficult to exceed 5V. However, in the actual use of batteries, there are many scenarios where voltages exceeding 5V are required, such as electric vehicles (EV), power tools (PT), energy storage systems (ESS), etc. Even in the mobile phone market, in order to meet the needs of fast charging, the open circuit voltage of the battery cell needs to be increased. At present, the method of connecting multiple lithium-ion batteries in series is generally used to increase the output voltage, but there are many problems with the series connection of multiple lithium-ion batteries, such as: the capacity difference between individual lithium-ion batteries leads to a low overall energy density (Energy Density); the series connection of wires and contact resistance introduces additional electronic resistance, resulting in heat waste and affecting battery life; the higher the voltage, the more lithium-ion batteries are required, which increases the difficulty of battery management. In order to solve the above problems, the concept of high-output voltage battery was proposed, which uses the internal series connection of lithium-ion batteries to achieve high voltage output of a single battery, reduce the total heat generated by the battery, and reduce the temperature rise during use.

[0004] The prior art series battery directly connects two electrode assemblies in series in the same packaging bag, without ion insulation between the two series electrode assemblies. If the battery voltage increases, the electrolyte will be decomposed under high voltage conditions, which will cause the battery to fail. In addition, the two electrode assemblies will have an internal short circuit due to the voltage difference between the pole pieces, which will also cause the battery to fail. For the above reasons, the solutions currently proposed are only applicable to solid electrolyte batteries. However, mainstream lithium batteries use liquid electrolytes, so the above solutions are difficult to promote. Summary of the invention

[0005] The purpose of the present application is to provide an electrochemical device that can not only achieve high voltage output but also reduce the temperature rise of the electrochemical device.

[0006] The first aspect of the present application provides an electrochemical device, comprising a separator, the separator is sealed and connected to an outer package, and independent cavities are formed on both sides of the separator, each cavity contains an electrode assembly and an electrolyte, and the electrode assemblies in adjacent cavities are connected in series through tabs, and the separator includes an ion insulating layer. The water permeability of the separator is less than or equal to 10 -3 g / (day·m 2 The seal thickness T and the seal width W of the partition and the outer package satisfy 0.01≤T / W≤0.05.

[0007] In one embodiment of the present application, the seal width W is 1 mm to 7 mm.

[0008] In one embodiment of the present application, the cavity is a sealed cavity.

[0009] In one embodiment of the present application, the material of the ion insulating layer includes at least one of a polymer material, a metal material and a carbon material.

[0010] In one embodiment of the present application, the polymer material includes polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyetheretherketone, polyimide, polyamide, polyethylene glycol, polyamideimide, polycarbonate, cyclic polyolefin, polyphenylene sulfide, polyvinyl acetate, polytetrafluoroethylene, polymethylene naphthalene, polyvinylidene fluoride, polyethylene naphthalate, polypropylene carbonate, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-co-chlorotrifluoroethylene), silicone, vinylon, polypropylene, anhydride-modified polypropylene, polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, ethylene-acrylic acid copolymer, ethylene-vinyl alcohol copolymer, polyvinyl chloride, polystyrene, polyether nitrile, polyurethane, polyphenylene ether, polyester, polysulfone, amorphous α-olefin copolymer and at least one of its derivatives. The metal material includes at least one of Ni, Ti, Cu, Ag, Au, Pt, Fe, Co, Cr, W, Mo, Al, Mg, K, Na, Ca, Sr, Ba, Si, Ge, Sb, Pb, In, Zn, stainless steel, and a combination or alloy thereof. The carbon material includes at least one of carbon felt, carbon film, carbon black, acetylene black, fullerene, conductive graphite film, or graphene film.

[0011] In one embodiment of the present application, the separator further comprises an encapsulation layer, which is arranged at the edges of the ion insulating layer or on the entire surface thereof, and the melting point of the material of the encapsulation layer is 120 to 160°C.

[0012] In one embodiment of the present application, the encapsulation layer includes at least one of polypropylene, anhydride-modified polypropylene, polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, ethylene-acrylic acid copolymer, ethylene-vinyl alcohol copolymer, polyvinyl chloride, polystyrene, polyether nitrile, polyurethane, polyamide, polyester, amorphous α-olefin copolymer and its derivatives.

[0013] In one embodiment of the present application, the separator has a thickness of 6 to 100 μm.

[0014] In one embodiment of the present application, the ion insulating layer is a single layer or multi-layer structure.

[0015] In one embodiment of the present application, it has at least one of the following features: (a) The water permeability of the partition is less than or equal to 10 -4 g / (day·m 2 ·Pa) / 3mm; (b) the separator has a thickness of 10 to 40 μm; (c) The melting point of the material of the ion insulating layer is ≥ 165°C.

[0016] In one embodiment of the present application, the structure of the electrode assembly includes a winding structure or a stacked structure.

[0017] A second aspect of the present application provides an electronic device, which includes the electrochemical device provided by the first aspect of the present application.

[0018] The electrochemical device provided by the present application has a partition sealed to the outer packaging, and independent cavities are formed on both sides of the partition. The electrode assemblies and electrolyte on both sides of the partition are completely separated, which not only ensures the normal operation of the electrode assemblies on both sides, but also the good sealing is conducive to improving the safety of the electrochemical device. In addition, the partition has the characteristics of ion insulation, so it can avoid high-voltage decomposition of the electrolyte and short circuit in the electrode assembly. The electrode assemblies on both sides of the partition are connected in series, and the electrochemical device not only achieves high voltage output, but also reduces the total heat generation of the battery cell and reduces the temperature rise during use. By limiting the water permeability of the partition to less than or equal to 10 -3 g / (day·m 2 ·Pa) / 3mm and the seal thickness T and seal width W of the separator and the outer package seal satisfy 0.01≤T / W≤0.05, which can improve the water resistance and environmental stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention and the technical solutions of the prior art, the following briefly introduces the drawings required for use in the embodiments and the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.

[0020] Figure 1 A schematic diagram of the structure of an electrochemical device in one embodiment of the present application; Figure 2 This is a schematic diagram of the cross-sectional structure of a partition in one embodiment of the present application; Figure 3 This is a schematic diagram of the structure of a partition in one embodiment of the present application; Figure 4 Schematic diagram of the electrochemical device structure of Comparative Example 1; Figure 5 Schematic diagram of the electrochemical device structure of Comparative Example 2; Figure 6 Schematic diagram of the electrochemical device structure of Comparative Example 3. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0022] The electrochemical device of the present application can be any electrochemical device known to those skilled in the art, such as a lithium-ion battery, a sodium-ion battery, a magnesium-ion battery, a supercapacitor, etc., and the following description is made using a lithium-ion battery as an example. Those skilled in the art should understand that the following description is only for illustrative purposes and does not limit the scope of protection of the present application.

[0023] The present application provides an electrochemical device, a typical embodiment of which is as follows Figure 1 The invention comprises a separator 1, which is sealed and connected to an outer package 3, and separate cavities are formed on both sides of the separator 1, each cavity contains an electrode assembly 2 and an electrolyte, and adjacent electrode assemblies 2 are connected in series through tabs, which may be the positive tab 4 of the electrode assembly 201 and the negative tab 5 of the electrode assembly 202 connected in series, or the negative tab 5 of the electrode assembly 201 and the negative tab 4 of the electrode assembly 202 connected in series. The separator 1 comprises an ion insulating layer for ion insulation. The cavity is a sealed cavity.

[0024] In the present application, the water permeability of the partition is less than or equal to 10 -3 g / (day·m 2The greater the water permeability of the separator, the easier it is for water vapor in the environment to penetrate into the battery through the separator, resulting in an increase in the water content in the non-aqueous electrolyte, an increase in the battery thickness, and a reduction in the battery life.

[0025] The seal thickness T (unit: mm) and the seal width W (unit: mm) of the separator and the outer package satisfy 0.01≤T / W≤0.05. The ratio of T / W is within the above range, which can ensure good sealing of the battery and improve the service life of the battery. When T / W is too small, the seal thickness may be insufficient, the sealing effect is not good, and the environmental stability of the battery is reduced. For example, water vapor in the environment can easily penetrate into the battery, resulting in an increase in the water content in the battery, electrolyte decomposition, and reduced battery life; when the ratio of T / W is too large, the seal width W may be too small, and there is also a poor sealing effect, resulting in reduced environmental stability of the battery. For example, water vapor in the environment can easily penetrate into the battery, resulting in an increase in the water content in the battery, electrolyte decomposition, and other problems, reducing the service life of the battery. In the present application, the seal thickness and seal width are not particularly limited, as long as the purpose of the present invention can be achieved, for example, the seal width is preferably 1mm to 7mm. In the present application, the seal thickness refers to the thickness of the sealing material in the sealing area; the seal width refers to the width of the sealing material in the sealing area. The sealing area refers to the area where the partition and the outer packaging are sealed together. During the sealing process, the polymer material of the inner layer of the outer packaging and the polymer material in the partition are sealed together by heat pressing to form a sealing area. Therefore, the seal thickness includes the thickness after the polymer material in the partition and the polymer material in the inner layer of the outer packaging are fused. The seal width refers to the width of the sealing area formed by the polymer material in the partition and the polymer material in the inner layer of the outer packaging after hot pressing. The seal thickness direction is the overlapping direction of the outer packaging and the partition, and the seal width direction is the distance between the two seal edges.

[0026] In some embodiments of the present application, the partition is sealed and connected to the outer packaging, and independent cavities are formed on both sides of the partition. The electrode assemblies and electrolytes on both sides of the partition are completely separated, which can not only ensure the normal operation of the electrode assemblies on both sides, but also the good sealing is conducive to improving the safety and environmental stability of the electrochemical device. In addition, the partition has the characteristics of ion insulation, so high-voltage decomposition of the electrolyte and short circuits in the electrode assemblies can be avoided. The electrode assemblies on both sides of the partition are connected in series, and the electrochemical device not only achieves high-voltage output, but also reduces the total heat generation of the battery cell and reduces the temperature rise during use. In addition, the water permeability of the partition is limited to the above range, which can more effectively avoid safety problems when the electrochemical device works in a high humidity environment; the ratio of the seal thickness T to the seal width W is limited to the above range, which can more effectively achieve the sealing of the electrochemical device and further improve the safety of the electrochemical device.

[0027] The structure of the ion insulating layer is not particularly limited as long as the purpose of the present invention can be achieved. For example, the ion insulating layer may have a single-layer structure or a multi-layer composite structure.

[0028] In some embodiments of the present application, the material of the ion insulating layer includes at least one of a polymer material, a metal material, a carbon material or a composite material thereof.

[0029] The polymer material is not particularly limited, as long as the present invention can be achieved, any material known to those skilled in the art can be used, for example, the polymer material may include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyetheretherketone, polyimide, polyamide, polyethylene glycol, polyamideimide, polycarbonate, cyclic polyolefin, polyphenylene sulfide, polyvinyl acetate, polytetrafluoroethylene, polymethylene naphthalene, polyvinylidene fluoride, polyethylene naphthalate, polypropylene carbonate, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-co-chlorotrifluoroethylene), silicone, vinylon, polypropylene, anhydride-modified polypropylene, polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, ethylene-acrylic acid copolymer, ethylene-vinyl alcohol copolymer, polyvinyl chloride, polystyrene, polyether nitrile, polyurethane, polyphenylene ether, polyester, polysulfone, amorphous α-olefin copolymer and at least one of its derivatives.

[0030] The metal material is not particularly limited, and any material known to those skilled in the art can be used as long as the purpose of the present invention can be achieved, for example, it can include at least one of Ni, Ti, Cu, Ag, Au, Pt, Fe, Co, Cr, W, Mo, Al, Mg, K, Na, Ca, Sr, Ba, Si, Ge, Sb, Pb, In, Zn, stainless steel, and combinations or alloys thereof. Preferably, a metal material with good anti-oxidation and reduction properties in a lithium-ion battery environment can be selected.

[0031] The carbon material includes at least one of carbon felt, carbon film, carbon black, acetylene black, fullerene, conductive graphite film or graphene film. In some embodiments of the present application, the ion insulating layer preferably uses a polymer material. Since the density of the polymer material is small, the weight of the inactive substance can be reduced, thereby increasing the mass energy density of the electrode assembly. In addition, the ion insulating layer uses a polymer material, which has a lower probability of generating debris under mechanical abuse (nail penetration, impact, extrusion, etc.) and has a better wrapping effect on the mechanically damaged surface. Therefore, the safety margin under the above-mentioned mechanical abuse can be improved, and the safety test pass rate can be improved.

[0032] In some embodiments of the present application, the ion insulating layer preferably uses metal materials, which have strong isolation reliability, better toughness and density than polymer materials, and can be processed to be thinner. When the ion insulating layer preferably uses a carbon material film, the product has excellent safety performance, especially excellent high-temperature reliability, and has the function of separating the two sides of the battery cell when the battery cell body is damaged.

[0033] In some embodiments of the present invention, the separator further comprises an encapsulation layer 102, and the encapsulation layer 102 can be disposed on both sides of the ion insulating layer 101, such as Figure 2 The encapsulation layer 102 is used to seal and connect the ion insulating layer 101 to the outer package. In other embodiments, the encapsulation layer 102 can also be disposed on the outer package.

[0034] In some embodiments of the present application, the encapsulation layer is disposed at the edges of the ion insulating layer or on the entire surface thereof. When the encapsulation layer is disposed at the edges of the ion insulating layer, the width of the encapsulation layer is not particularly limited, as long as it is greater than the seal width to ensure the required seal width. Figure 3 As shown, the encapsulation layer 102 is arranged at the edges of the surface of the ion insulating layer 101, which reduces the coating amount and proportion of the encapsulation layer as much as possible, reduces the proportion of inactive substances, and can improve the energy density of the battery cell. The encapsulation layer is arranged on the entire surface of the ion insulating layer, which can effectively reduce the water permeability of the separator. When the electrochemical device works in a high air humidity environment, it can more effectively avoid the short circuit of the electrochemical device due to water absorption by the separator, or even a safety failure.

[0035] In some embodiments of the present application, the encapsulation layer is arranged at the edges of the surface of the ion insulating layer, the ion insulating layer is a conductive material, and the outermost side of at least one of the electrode assemblies on both sides of the separator adjacent to the separator is a diaphragm.

[0036] In some embodiments of the present application, the encapsulation layer is arranged at the edges of the surface of the ion insulating layer, the ion insulating layer is an insulating material, and the outermost sides of the electrode assemblies on both sides of the partition adjacent to the partition can be one of a diaphragm, a positive electrode collector, a negative electrode collector, a positive electrode active material, and a negative electrode active material.

[0037] In some embodiments of the present application, the encapsulation layer is arranged on the entire surface of the ion insulating layer, and the outermost sides of the electrode assemblies adjacent to the separator on both sides of the separator can be one of a separator, a positive electrode collector, a negative electrode collector, a positive electrode active material, and a negative electrode active material.

[0038] In the present application, the material of the encapsulation layer is not particularly limited as long as the purpose of the present invention can be achieved. Materials known to those skilled in the art can be used. For example, the encapsulation layer material includes at least one of polypropylene, anhydride-modified polypropylene, polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, ethylene-acrylic acid copolymer, ethylene-vinyl alcohol copolymer, polyvinyl chloride, polystyrene, polyether nitrile, polyurethane, polyamide, polyester, amorphous α-olefin copolymer and their derivatives.

[0039] Of course, the encapsulation layer of the present invention also has the function of ion insulation when covering the entire surface of the ion insulation layer. In the present application, for the sake of convenience, the separator is divided into an ion insulation layer and an encapsulation layer, which does not mean that the encapsulation layer has no ion insulation. For example, when both sides of the ion insulation layer are completely covered with the encapsulation layer, the ion insulation layer and the encapsulation layer play an ion insulation role together.

[0040] In some embodiments of the present application, the thickness of the separator is 6 to 100 μm. The separator not only has the characteristics of ion insulation, but also has a certain mechanical strength. Therefore, if the separator is too thin, the mechanical strength is poor, and it is easy to cause damage, affecting the performance and even safety of the electrochemical device. If it is too thick, it will affect the conduction of electrons and reduce the energy density of the electrochemical device, so that the performance of the electrochemical device is limited.

[0041] In an embodiment of the present application, when the encapsulation layer is only located in the sealing area, the thickness of the partition is the thickness of the ion insulating layer itself. When the encapsulation layer covers the entire ion insulating layer, the thickness of the partition is the sum of the thickness of the ion insulating layer and the thickness of the encapsulation layer on both sides of the ion insulating layer. The thickness of the encapsulation layer on both sides of the ion insulating layer can be the same or different, as long as the purpose of the present invention can be achieved. For example, the thickness of the encapsulation layer on both sides of the ion insulating layer is the same.

[0042] In some embodiments of the present application, the electrochemical device has at least one of the following features: (a) The water permeability of the partition is less than or equal to 10 -4 g / (day·m 2 ·Pa) / 3mm; (b) the separator has a thickness of 10 to 40 μm; (c) the melting point of the material of the encapsulation layer is 120 to 160°C; (d) The melting point of the material of the ion insulating layer is greater than or equal to 165°C.

[0043] In the present application, the partition is sealed and connected to the outer packaging, which means that the packaging layer of the partition is sealed and connected to the inner layer of the outer packaging, so that each independent sealed cavity is formed in the electrochemical device, so that the multiple electrode assemblies can achieve ion insulation between the multiple electrode assemblies of the liquid series battery, avoid the safety hazards of internal short circuit or high-pressure decomposition of the electrolyte, and improve the safety performance of the electrochemical device. Therefore, limiting the melting point of the packaging material to the above temperature is more conducive to achieving a sealed connection between the partition and the outer packaging.

[0044] In some embodiments of the present application, the structure of the electrode assembly includes a winding structure or a stacked structure.

[0045] In some embodiments of the present application, the structure of the electrode assembly is a winding structure, and the electrode assembly includes a single pole ear or multiple pole ears. The electrode assembly includes a single pole ear, which is a positive pole ear and a negative pole ear respectively drawn from the positive pole sheet and the negative pole sheet. The electrode assembly includes multiple pole ears, which can be a positive pole ear and a negative pole ear respectively drawn from each circle of the positive pole sheet and the negative pole sheet, or a positive pole ear and a negative pole ear respectively drawn from two or more circles of the positive pole sheet and the negative pole sheet. Finally, an electrode assembly with a winding structure includes multiple groups of positive pole ears and negative pole ears, and then the pole ear leads are transferred by transfer welding.

[0046] In some embodiments of the present application, the structure of the electrode assembly is a stacked structure, and the electrode assembly includes multiple pole tabs, which can be a positive pole tab and a negative pole tab respectively led out from each layer of the positive pole sheet and the negative pole sheet. Finally, an electrode assembly with a stacked structure contains multiple groups of positive pole tabs and negative pole tabs, and then the pole tab leads are transferred by adapter welding.

[0047] In the present application, the welding method is not particularly limited as long as the purpose of the present application can be achieved, for example, laser welding, ultrasonic welding or resistance welding.

[0048] The electrode assembly mentioned in the present application may be an electrode assembly including a positive electrode sheet, a negative electrode sheet and a separator, and the above electrode assembly is used as an example for description. Those skilled in the art should understand that the following description is only for illustration and does not limit the scope of protection of the present application.

[0049] In the present application, there is no particular restriction on the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the positive electrode sheet generally includes a positive current collector and a positive active material. In the present application, the positive current collector is not particularly limited, and can be any positive current collector known in the art, such as copper foil, aluminum foil, aluminum alloy foil, and composite current collector. The positive active material is not particularly limited, and can be any positive active material of the prior art, for example, the positive active material includes at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, or lithium manganese iron phosphate. In the present application, there is no particular restriction on the thickness of the positive current collector and the positive active material, as long as the purpose of the present application can be achieved. For example, the thickness of the positive current collector is 8 to 12 μm, and the thickness of the positive active material is 30 to 120 μm.

[0050] In some preferred embodiments of the present application, the positive electrode sheet may further include a conductive layer, and the conductive layer is located between the positive electrode current collector and the positive electrode active material layer. The composition of the conductive layer is not particularly limited, and may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder.

[0051] In some embodiments of the present application, the negative electrode sheet is not particularly limited, as long as the purpose of the present application can be achieved. For example, the negative electrode sheet generally comprises a negative electrode current collector and a negative electrode active material. In the present application, the negative electrode current collector is not particularly limited, and any negative electrode current collector known in the art, such as copper foil, aluminum foil, aluminum alloy foil, and composite current collector, etc., can be used. The negative electrode active material is not particularly limited, and any negative electrode active material known in the art can be used. For example, it can include at least one of artificial graphite, natural graphite, mesophase carbon microspheres, silicon, silicon carbon, silicon oxides, soft carbon, hard carbon, lithium titanate, or niobium titanate. In the present application, the thickness of the negative electrode current collector and the negative electrode active material is not particularly limited, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 6 to 10 μm, and the thickness of the negative electrode active material is 30 to 120 μm.

[0052] In some preferred embodiments of the present application, the negative electrode plate may further include a conductive layer, and the conductive layer is located between the negative electrode current collector and the negative electrode active material layer. The composition of the conductive layer is not particularly limited, and may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder.

[0053] The conductive agent described above is not particularly limited, and any conductive agent known in the art can be used, as long as the purpose of the present application can be achieved. For example, the conductive agent can include at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fiber or graphene. The adhesive described above is not particularly limited, and any adhesive known in the art can be used, as long as the purpose of the present application can be achieved. For example, the adhesive can include at least one of styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE) or sodium carboxymethyl cellulose (CMC-Na).

[0054] In some embodiments of the present application, the separator (also called isolation membrane) is not particularly limited as long as the purpose of the present application can be achieved. For example, the thickness of the separator can be 5 to 15 μm, and the separator can include a polymer or inorganic material formed by a material that stabilizes the electrolyte of the present application.

[0055] For example, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer may be a nonwoven fabric, a film or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance.

[0056] For example, the inorganic layer includes inorganic particles and a binder, and the inorganic particles are not particularly limited, for example, aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder is not particularly limited, for example, it can be selected from one or more combinations of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene. The polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).

[0057] The tabs mentioned in this application refer to metal conductors drawn from the positive electrode sheet or the negative electrode sheet, which are used to connect other parts of the electrochemical device in series or in parallel. The positive tabs are drawn from the positive electrode sheet, and the negative tabs are drawn from the negative electrode sheet.

[0058] The electrolyte described in the present application may contain a lithium salt and a non-aqueous solvent. In the present application, the lithium salt is not particularly limited, and any lithium salt known in the art can be used, as long as the purpose of the present application can be achieved. For example, the lithium salt may include at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3 or LiPO2F2. For example, LiPF6 can be selected as the lithium salt. In the present application, the non-aqueous solvent is not particularly limited, as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include at least one of a carbonate compound, a carboxylate compound, an ether compound, a nitrile compound, and other organic solvents.

[0059] For example, the carbonate compound may include at least one of diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, and trifluoromethylethylene carbonate.

[0060] There is no special restriction on the outer packaging in the present application, as long as the purpose of the present application can be achieved. For example, the outer packaging may include an inner layer and an outer layer, and the inner layer is sealed and connected to the partition, so the material of the inner layer may include a polymer material, thereby achieving a good sealing effect; at the same time, the combination of the inner layer and the outer layer can effectively protect the internal structure of the electrochemical device. There is no special restriction on the inner layer material in the present application, as long as the purpose of the present application can be achieved. For example, the material of the inner layer includes at least one of polypropylene, polyester, parahydroxybenzaldehyde, polyamide, polyphenylene ether, polyurethane, etc. In the present application, there is no special restriction on the outer layer material, as long as the purpose of the present application can be achieved. For example, the material of the outer layer includes aluminum foil, aluminum oxide layer, silicon nitride layer, Ni, Cu, and at least one of Al in Ag.

[0061] There is no particular limitation on the thickness of the outer packaging in the present application, as long as the purpose of the present application can be achieved. For example, the thickness of the outer packaging is 60 to 200 μm, and the outer packaging of the above thickness can effectively protect the internal structure of the electrochemical device.

[0062] The present application has no particular restrictions on the sealing connection method between the partition and the outer packaging, as long as the purpose of the present application can be achieved. For example, the sealing method can be performed by hot pressing. In the present application, the hot pressing conditions are not particularly limited, as long as the purpose of the present application can be achieved, for example, the hot pressing temperature is 150 to 220°C, and the hot pressing pressure is 0.1 to 0.6Mpa.

[0063] The present application also provides an electronic device, which includes an electrochemical device provided in the present application. The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. For example, the electronic device includes but is not limited to a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0064] The method for preparing the electrochemical device of the present application is not particularly limited, and any method known in the art may be used. For example, the present application may be prepared by the following preparation method: (1) Preparation of negative electrode sheet: The negative electrode active material and solvent are mixed into a slurry and stirred evenly. The slurry is evenly coated on the negative electrode sheet and dried to obtain a single-sided coated negative electrode sheet. The above steps are repeated on the other surface of the negative electrode sheet to obtain a double-sided coated negative electrode sheet. Then, the negative electrode sheet is cut for use. The coating thickness of the negative electrode active material on one surface is 70 μm.

[0065] (2) Preparation of positive electrode sheet: The positive electrode active material and solvent are mixed into a slurry and stirred evenly. The slurry is evenly coated on the positive electrode sheet and dried to obtain a single-sided coated positive electrode sheet. The above steps are repeated on the other surface of the positive electrode sheet to obtain a double-sided coated positive electrode sheet. Then, the positive electrode sheet is cut for standby use. The coating thickness of the positive electrode active material on one surface is 65 μm.

[0066] (3) Preparation of electrolyte: The lithium salt and the non-aqueous solvent are mixed and stirred to obtain an electrolyte containing a lithium salt concentration of 30%.

[0067] (4) Preparation of electrode assemblies: The negative electrode sheet, separator, and positive electrode sheet are stacked and the layers are fixed together for use. Each electrode assembly includes a positive electrode tab and a negative electrode tab. Repeating the above steps can obtain multiple electrode assemblies. The structure of the electrode assembly can be a winding structure or a stacked structure.

[0068] (5) Partition: The partition provided in this application may be used.

[0069] (6) Electrode assembly: The outer package is placed in an assembly fixture, and then the electrode assembly and the separator are spaced apart, and the outer package is adjacent to the electrode assembly, and finally sealed to obtain an assembled electrode assembly.

[0070] (7) Liquid injection packaging: The electrolyte is injected into the two cavities of the assembled electrode assembly separately, and all the tabs of the electrode assembly are led out of the aluminum-plastic film for subsequent processing.

[0071] (8) Series connection: The positive electrode tab of one electrode assembly and the negative electrode tab of another electrode assembly are connected together by laser welding to achieve series connection, and the battery assembly is completed.

[0072] The electrochemical device provided in the present application may include two electrode assemblies or three or more electrode assemblies. The preparation method of the electrochemical device including two electrode assemblies or three or more electrode assemblies may refer to the preparation method of the electrochemical device described above.

[0073] The terms used in this application are generally terms commonly used by those skilled in the art. If there is any inconsistency with commonly used terms, the terms in this application shall prevail.

[0074] Specifically, in this application, the following terms have the following meanings: Test method: Water vapor permeability: Prepare a film of a certain thickness (such as 60μm), place it on a clamping mechanism, and press the edge with a large rubber pressure. Create an environment with fixed temperature and humidity on one side A of the device, and set a water vapor mass spectrometer detection probe on the other side B. Gas exchange on both sides can only pass through the film. During the test, the film is first fixed, and the cavity B is evacuated to exhaust the water vapor inside. Then turn on the mass spectrometer, which continuously receives water vapor that penetrates from cavity A and converts it into an electrical signal output. Continue the above test for 24 hours or longer to obtain the total amount of water permeation m during this period of time. The total amount of permeation m divided by time, water vapor partial pressure, permeation area, and film thickness can obtain the water vapor permeability, unit g / (day·m 2 ·Pa) / 3mm.

[0075] 0.1C discharge energy density: The electrochemical device was left at room temperature for 30 minutes, and then charged at a constant current of 0.05C to a voltage of 4.4V (rated voltage), and then discharged at a rate of 0.05C to 3.0V. The above charge / discharge steps were repeated for 3 cycles to complete the formation of the electrochemical device to be tested. After the formation of the electrochemical device was completed, it was charged at a constant current of 0.1C to a voltage of 4.4V, and then discharged at a rate of 0.1C to 3.0V, and its discharge capacity was recorded, and then its energy density at 0.1C discharge was calculated: Energy density (Wh / L) = discharge capacity (Wh) / electrochemical device volume size (L) Packaging strength between partition and outer packaging: After sealing the partition and the outer packaging, take the flat part and cut it into samples with a width of 8mm. Clamp the partition at one end of the sample with a tensile gauge, and clamp the other end with another clamp of the tensile gauge, and pull it apart at a tensile speed of 20mm / min until the partition and the packaging tape are completely separated. The peak value during the recording process is the tensile value.

[0076] Thickness growth rate of electrochemical device after 7 days storage at 65℃_90%RH: The cell was charged at 1.0C constant current to 4.45V, then charged at constant voltage until the current dropped to 0.05C, charging stopped, and then the cell was removed after standing for 1 hour, and the initial thickness T1 of the cell was measured. The cell was stored in a 65℃_90%RH environment for seven days, and its thickness T2 was tested, and compared with the thickness growth at the beginning of storage, the growth rate was (T2-T1) / T1×100%.

[0077] 7.6V voltage platform self-discharge rate K: The lithium-ion battery was discharged at a current of 0.5C to 6.0V (series battery), and then left to stand for 5 minutes. Then, the lithium-ion battery was charged at a constant current of 0.5C to 7.6V, and then charged at a constant voltage of 7.6V to a current of 0.05C, and left to stand for two days in an environment of 25℃±3℃, and the voltage OCV1 at this time was tested and recorded. Then, the lithium-ion battery was left to stand for two days in an environment of 25℃±3℃, and the voltage OCV2 at this time was tested and recorded, and the K value was obtained by the following formula: K (mV / h) = (OCV2-OCV1) / 48h×1000.

[0078] Nail penetration test: The electrochemical device to be tested is charged at a constant current of 0.05 C to a voltage of 4.45 V (rated voltage of comparative example 1) or 8.90 V (other comparative examples and all embodiments), and then charged at a constant voltage to a current of 0.025C (cut-off current) to fully charge the battery, and record the appearance of the electrochemical device before the test. The electrochemical device is subjected to a nail penetration test in an environment of 25±3°C, with a steel nail diameter of 4mm and a penetration speed of 30mm / s. The nail penetration positions are located 15mm from the edge of the positive pole tab electrode assembly and 15mm from the edge of the negative pole tab electrode assembly, respectively. The test is stopped after 3.5min or when the surface temperature of the electrode assembly drops to 50°C. Ten cells are grouped together to observe the battery status during the test, and the battery is judged as not burning or exploding.

[0079] Discharge temperature rise: The test temperature is 25°C. A temperature probe is bonded to the center of the cell surface to monitor the temperature of the cell body, and foam is wrapped on the cell surface to weaken the heat exchange between the cell and the contact. The test process is as follows: discharge at a constant current of 0.2C to 6 V (6V for series cells) or 3V (3V for a single cell in the comparative example, the same below), then charge at a constant current of 0.5C to 8.4V or 4.2V, charge at 0.2C to 8.9V or 4.45V, and let stand for 120 minutes until the center temperature of the cell drops to room temperature 25°C. Use the same power of 15W to discharge and monitor the temperature rise of the cell body during the discharge process.

[0080] Embodiment 1: (1) Preparation of negative electrode sheet: Mix the negative electrode active materials artificial graphite, conductive carbon black (Super P), and styrene-butadiene rubber (SBR) in a weight ratio of 96:1.5:2.5, add deionized water as a solvent, prepare a slurry with a solid content of 70wt%, and stir evenly. The slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 10μm, and dried at 110°C to obtain a negative electrode sheet with a coating thickness of 150μm and a single-sided negative electrode active material layer. Repeat the above steps on the other surface of the negative electrode sheet to obtain a negative electrode sheet with a double-sided negative electrode active material layer. Then, cut the negative electrode sheet into a size of 41mm×61mm for standby use.

[0081] (2) Preparation of positive electrode sheet: Mix the positive electrode active materials lithium cobalt oxide (LiCoO2), conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) in a weight ratio of 97.5:1.0:1.5, add N-methylpyrrolidone (NMP) as a solvent, prepare a slurry with a solid content of 75wt%, and stir evenly. The slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and dried at 90°C to obtain a positive electrode sheet with a positive electrode active material layer thickness of 100μm. Repeat the above steps on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode sheet with a positive electrode active material layer coated on both sides. Then, the positive electrode sheet is cut into a specification of 38mm×58mm for standby use.

[0082] (3) Preparation of electrolyte: In a dry argon atmosphere, organic solvents ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) were first mixed at a mass ratio of EC:EMC:DEC = 30:50:20. Then, lithium salt lithium hexafluorophosphate (LiPF6) was added to the organic solvent to dissolve and mix well to obtain an electrolyte with a lithium salt concentration of 1.15 mol / L.

[0083] (4) Preparation of electrode assembly A and electrode assembly B: The separator, double-sided coated negative electrode sheet, separator, and double-sided coated positive electrode sheet are stacked in sequence to form a laminate, and then the four corners of the entire laminate structure are fixed for standby use. Each electrode assembly includes a positive electrode tab and a negative electrode tab, and the separator is a polyethylene (PE) film with a thickness of 15 μm.

[0084] (5) Separator: The thickness of the separator is 30 μm. The ion insulating layer is made of PP with a melting point of 165°C and a thickness of 10 μm. The encapsulation layers on both sides are made of PP with a melting point of 140°C and a thickness of 10 μm on both sides. The water vapor permeability of the separator is 3×10 -4 g / (day·m 2 ·Pa) / 3mm.

[0085] (6) Assembly of electrode assembly A: Place the aluminum-plastic film 1 with the pits formed in it into an assembly fixture with the pits facing upwards, place the electrode assembly A in the pits with the diaphragm facing upwards, and then place the separator on the electrode assembly A so that the edges are aligned and apply external force to compact it to obtain an assembled semi-finished product.

[0086] (7) Assembly of electrode assembly B: Place the semi-finished assembly in the assembly fixture with the separator facing upward, place the electrode assembly B with the separator facing downward, align the edges, apply external force to press tightly, and then cover the other aluminum-plastic film with the pit facing downward on the electrode assembly B, and heat-seal the surroundings by hot pressing to obtain an assembled electrode assembly. The hot pressing temperature is 185°C, the hot pressing pressure is 0.5Mpa, the width of the sealing area is 2mm, the sealing thickness with the packaging bag is 0.3mm, and the thickness of the polymer layer in the sealing area is about 0.04mm.

[0087] (8) Liquid injection packaging: The electrolyte is injected into the two cavities of the assembled electrode assembly separately, and all the tabs of the electrode assemblies A and B are led out of the aluminum-plastic film.

[0088] (9) Series connection: The positive electrode tab of electrode assembly A and the negative electrode tab of electrode assembly B are connected together by laser welding to achieve series connection, and the battery assembly is completed.

[0089] Example 2 The ion insulating layer is a Ti metal foil with a thickness of 10 μm, and the rest is the same as in Example 1.

[0090] Example 3 The ion insulating layer is a SUS metal foil with a thickness of 10 μm. The rest is the same as in Example 1.

[0091] Example 4 The ion insulating layer is a PI film with a thickness of 10 μm, and the rest is the same as in Example 1.

[0092] Example 5 The thickness of the partition is 6 μm, the ion insulating layer is Ti metal foil with a thickness of 6 μm, and a packaging layer with a thickness of 10 μm and a width of 2 mm is set around the edges of the ion insulating layer. The packaging layer material is PP with a melting point of 140°C. The rest is the same as Example 1.

[0093] Example 6 The thickness of the separator is 100 μm, the thickness of the ion insulating layer is 80 μm, the thickness of the encapsulation layers on both sides is 10 μm respectively, and the rest is the same as in Example 1.

[0094] Example 7 The thickness of the separator is 15 μm, the thickness of the ion insulating layer is 15 μm, and a packaging layer with a thickness of 10 μm and a width of 2 mm is set around the edges of the ion insulating layer. The packaging layer material is PP with a melting point of 140° C., and the rest is the same as Example 1.

[0095] Example 8 The preparation steps (1) to (3) are the same as those in Example 1.

[0096] (4) Preparation of electrode assembly A and electrode assembly B: The double-sided coated negative electrode sheet, the separator, and the single-sided coated positive electrode sheet are stacked in sequence to form a laminate, with the uncoated surface of the positive electrode sheet facing outward, and then the four corners of the entire laminate structure are fixed for use. Each electrode assembly includes a positive electrode tab and a negative electrode tab, and the separator is a polyethylene (PE) film with a thickness of 15 μm.

[0097] (5) Separator: The thickness of the separator is 50 μm. The ion insulating layer is made of PP with a melting point of 165°C and a thickness of 15 μm. The encapsulation layers on both sides are made of PP with a melting point of 140°C and a thickness of 10 μm each. The water vapor permeability of the separator is 3×10 -4 g / (day·m 2 ·Pa) / 3mm.

[0098] (6) Assembly of electrode assembly A: Place the aluminum-plastic film with the pits formed in the assembly fixture with the pits facing upward, place the electrode assembly A in the pits with the uncoated surface of the positive electrode plate facing upward, and then place the separator on the electrode assembly A so that the edges are aligned and apply external force to compact it to obtain the assembled semi-finished product.

[0099] (7) Assembly of electrode assembly B: Place the semi-finished assembly in the assembly fixture with the separator facing upward, place the electrode assembly B with the separator facing downward, align the edges, apply external force to press tightly, and then cover the aluminum-plastic film with the pits facing downward on the electrode assembly B, and heat-seal the surroundings by hot pressing to obtain an assembled electrode assembly. The hot pressing temperature is 185°C, the hot pressing pressure is 0.5Mpa, the width of the sealing area is 2mm, the sealing thickness with the packaging bag is 0.3mm, and the thickness of the polymer layer in the sealing area is about 0.04mm.

[0100] (8) Liquid injection packaging: The electrolyte is injected into the two cavities of the assembled electrode assembly separately, and all the tabs of the electrode assemblies A and B are led out of the aluminum-plastic film.

[0101] (9) Series connection: The positive electrode tab of electrode assembly A and the negative electrode tab of electrode assembly B are connected together by laser welding to achieve series conduction, and the battery assembly is completed.

[0102] Example 9 The preparation steps (1) to (3) are the same as those in Example 1.

[0103] (4) Preparation of electrode assembly A and electrode assembly B: The double-sided coated negative electrode sheet, the separator, and the single-sided coated positive electrode sheet are stacked in sequence to form a stack, with the uncoated surface of the positive electrode sheet facing outward, and then the four corners of the entire stack structure are fixed for use. Each electrode assembly includes a positive electrode tab and a negative electrode tab, and the separator is a polyethylene (PE) film with a thickness of 15 μm.

[0104] (5) Separator: The thickness of the separator is 30 μm. The middle layer is made of PP with a melting point of 165°C and a thickness of 10 μm. The encapsulation layers on both sides are made of PP with a melting point of 140°C and a thickness of 10 μm each. The water vapor permeability of the separator is 3×10 -4 g / (day·m 2 ·Pa) / 3mm.

[0105] (6) Assembly of electrode assembly A: Place the aluminum-plastic film with the pits formed in the assembly fixture with the pits facing upward, place the electrode assembly A in the pits with the uncoated surface of the positive electrode plate facing upward, and then place the separator on the electrode assembly A so that the edges are aligned and apply external force to compact it to obtain the assembled semi-finished product.

[0106] (7) Assembly of electrode assembly B: Place the semi-finished assembly in the assembly fixture with the separator facing upward, place the uncoated surface of the positive electrode sheet of electrode assembly B facing downward on the separator, align the edges, apply external force to press tightly, and then cover the aluminum-plastic film with the pitted surface facing downward on electrode assembly B, and heat-seal the surroundings by hot pressing to obtain an assembled electrode assembly. The hot pressing temperature is 185°C, the hot pressing pressure is 0.5Mpa, the width of the sealing area is 2mm, the sealing thickness of the packaging bag is 0.3mm, and the thickness of the polymer layer in the sealing area is 0.04mm.

[0107] Preparation steps (8) and (9) are the same as in Example 1.

[0108] Example 10 The ion insulating layer is Ti metal foil with a thickness of 10 μm. The encapsulation layers on both sides are PP with a melting point of 140° C. and each is 10 μm. The rest is the same as in Example 8.

[0109] Embodiment 11 The ion insulating layer is Ti metal foil with a thickness of 10 μm. The encapsulation layers on both sides are PP with a melting point of 140° C. and each is 10 μm. The rest is the same as in Example 9.

[0110] Example 12 The encapsulation layer is anhydride-modified PP with a melting point of 130°C, and the water vapor permeability of the separator is 8×10 -5 g / (day·m 2 ·Pa) / 3mm, and the rest is the same as in Example 1.

[0111] Example 13 The thickness of the sealing area is 0.1 mm, the width of the sealing area is 2 mm, and the rest is the same as in Example 1.

[0112] Embodiment 14 The thickness of the sealing area is 0.05 mm, the width of the sealing area is 2 mm, and the rest is the same as in Example 1.

[0113] Embodiment 15 The preparation steps (1) to (4) are the same as those in Example 1.

[0114] (5) Preparation of electrode assembly C: The separator, double-sided coated negative electrode sheet, separator, and double-sided coated positive electrode sheet are stacked in sequence to form a laminate, and then the four corners of the entire laminate structure are fixed for use. Among them, the electrode assembly C includes a positive electrode tab and a negative electrode tab, and the separator is a polyethylene (PE) film with a thickness of 15 μm.

[0115] (6) Selection of separator A and separator B: The thickness of the separator is 30 μm, the ion insulating layer is PP with a melting point of 165°C and a thickness of 10 μm, the encapsulation layers on both sides are PP with a melting point of 140°C and a thickness of 10 μm each, and the water vapor permeability of the separator is 3×10 -4 g / (day·m 2 ·Pa) / 3mm.

[0116] (7) Assembly of electrode assembly A: Place the aluminum-plastic film with the pits formed in the assembly fixture with the pits facing upward, place the electrode assembly A in the pits with the diaphragm facing upward, and then place the separator on the electrode assembly A so that the edges are aligned and apply external force to compact it to obtain the assembled semi-finished product.

[0117] (8) Assembly of electrode assembly B: Place the semi-finished assembly in step (7) in an assembly fixture with separator A facing upward, place electrode assembly B with the separator surface facing downward on separator A, and then place separator B on electrode assembly B so that the edges are aligned. Apply external force to compact the semi-finished assembly.

[0118] (9) Assembly of electrode assembly C: Place the semi-finished product in step (8) in an assembly fixture, with separator B facing upward, and place the electrode assembly C with the separator surface facing downward on separator B, so that the edges are aligned, apply external force to press tightly, and then cover the aluminum-plastic film with the pit surface facing downward on the electrode assembly C, and heat-seal the surroundings by hot pressing to obtain an assembled electrode assembly. The hot pressing temperature is 185°C, the hot pressing pressure is 0.5Mpa, the width of the sealing area is 2mm, the sealing thickness of the packaging bag is 0.27mm, and the thickness of the polymer layer in the sealing area is about 0.05mm.

[0119] (10) Liquid injection packaging: The electrolyte is injected into the two cavities of the assembled electrode assembly separately, and all the tabs of the electrode assemblies A, B, and C are led out of the aluminum-plastic film.

[0120] (11) Series connection: The positive electrode tab of electrode assembly A and the negative electrode tab of electrode assembly B are connected together by laser welding to realize the series connection between the electrochemical devices containing electrode assemblies A and B. The positive electrode tab of electrode assembly B and the negative electrode tab of electrode assembly C are connected together by laser welding to realize the series connection between the electrochemical devices containing electrode assemblies B and C. The battery assembly is completed.

[0121] Example 16 Except that the partition A and the partition B are the same as those in Example 2, the rest is the same as that in Example 15.

[0122] Embodiment 17 The ion insulating layer is a carbon film with a thickness of 20 μm. A packaging layer with a thickness of 10 μm and a width of 2 mm is arranged around the edges of the ion insulating layer. The packaging layer material is PP with a melting point of 140° C. The rest is the same as in Example 1.

[0123] Embodiment 18 The ion insulating layer is a graphene film with a thickness of 20 μm. A packaging layer with a thickness of 10 μm and a width of 2 mm is arranged around the edges of the ion insulating layer. The packaging layer material is PP with a melting point of 140° C. The rest is the same as in Example 1.

[0124] Embodiment 19 The encapsulation layer is made of polyphenylene ether with a melting point of 120°C, and the water vapor permeability of the separator is 2.5×10 -4 g / (day·m 2 ·Pa) / 3mm, and the rest is the same as in Example 1.

[0125] Embodiment 20 (1) Preparation of negative electrode sheet: The negative electrode sheet was cut into a size of 41 mm×550 mm for later use. The rest was the same as in Example 1.

[0126] (2) Preparation of positive electrode sheet: The positive electrode sheet was cut into a size of 35 mm×547 mm for later use. The rest of the process was the same as in Example 1.

[0127] (3) Preparation of electrolyte: In a dry argon atmosphere, organic solvents ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) were first mixed at a mass ratio of EC:EMC:DEC = 30:50:20. Then, lithium salt lithium hexafluorophosphate (LiPF6) was added to the organic solvent to dissolve and mix well to obtain an electrolyte with a lithium salt concentration of 1.15 mol / L.

[0128] (4) Preparation of electrode assembly A and electrode assembly B: The separator, double-sided coated negative electrode sheet, separator, and double-sided coated positive electrode sheet are stacked, and then wound from one end to form a roll core, with the negative electrode sheet placed on the outermost side. Each electrode assembly includes a positive electrode tab and a negative electrode tab, and the separator is a polyethylene (PE) film with a thickness of 15 μm.

[0129] (5) Partition: The thickness of the partition is 30 μm. The middle layer is made of PP with a melting point of 165°C and a thickness of 10 μm. The encapsulation layers on both sides are made of PP with a melting point of 140°C and a thickness of 10 μm each. The water vapor permeability of the partition is 3×10 -4 g / (day·m 2 ·Pa) / 3mm.

[0130] (6) Assembly of electrode assembly A: Place the aluminum-plastic film 1 with the pits formed therein in an assembly fixture 1 with the pits facing upwards, place the electrode assembly A in the pits, and then place the separator on the electrode assembly A. Apply external force to compact the assembly to obtain a semi-finished product.

[0131] (7) Assembly of electrode assembly B: Place the semi-finished assembly in the assembly fixture 2 with the partition facing upward, place the electrode assembly B on the partition, apply external force to compress it, and then cover the punched aluminum-plastic film 2 with the pit surface facing downward on the electrode assembly B, and heat-seal it around by hot pressing to obtain an assembled electrode assembly. The hot pressing temperature is 185°C, the hot pressing pressure is 0.5Mpa, the width of the sealing area is 2mm, the sealing thickness of the packaging bag is about 0.27mm, and the thickness of the polymer layer in the sealing area is about 0.05mm.

[0132] (8) Liquid injection packaging: The electrolyte is injected into the two cavities of the assembled electrode assembly separately, and all the tabs of the electrode assemblies A and B are led out of the aluminum-plastic film.

[0133] (9) Series connection of electrode assemblies: The positive electrode tab of electrode assembly A and the negative electrode tab of electrode assembly B are connected together by laser welding to achieve series connection between electrode assemblies A and B. The battery assembly is completed.

[0134] Embodiment 21 The same as in Example 1 except that the thickness of the polymer seal area in the sealing area is 20 μm and the width of the sealing area is 2 mm.

[0135] Comparative Example 1 The preparation steps (1) to (3) are the same as those in Example 1.

[0136] (4) Preparation of electrode assembly A and electrode assembly B: Double-sided coated negative electrode sheet, separator, and double-sided coated positive electrode sheet are stacked in sequence to form a laminate, and then the four corners of the entire laminate structure are fixed for use. Each electrode assembly includes a positive electrode tab and a negative electrode tab. Among them, the separator is a polyethylene (PE) film with a thickness of 15 μm.

[0137] (5) Liquid injection packaging: Wrap the electrode assemblies A and B with aluminum foil, and then seal the package on all sides. Inject electrolyte into the sealed cavities where the electrode assemblies A and B are located, and charge them (charge at a constant current of 0.02C to 3.3V, and then charge at a constant current of 0.1C to 3.6V). Then, all the tabs of the electrode assemblies A and B are led out of the aluminum-plastic film.

[0138] (6) Series connection: The positive electrode tab of electrode assembly A and the negative electrode tab of electrode assembly B are connected together by laser welding to achieve series connection. The battery assembly is completed. The structural diagram is shown in the figure. Figure 4 shown.

[0139] Comparative Example 2 The preparation steps (1) to (4) are the same as those in Comparative Example 1.

[0140] (5) Packaging, liquid injection and connection: The tabs of electrode assemblies A and B are respectively led out along the length direction of the electrode assemblies and located on both sides of the electrode assemblies. The positive tabs are coated with sealant. The negative tab of electrode assembly A and the positive tab of electrode assembly B are welded together by laser welding to achieve series conduction between electrode assemblies A and B. The electrode assemblies A and B after the series connection are sealed in a contoured aluminum-plastic film. During packaging, in addition to sealing the top side of the outer contour, the positive tabs of electrode assemblies A and B are also sealed along the width direction of the electrode assemblies. The electrode assemblies A and B are respectively located in independent sealed cavities and the electrolyte is injected separately. After packaging, the positive tabs are led out on one side and the negative tabs are led out on the other side along the length direction of electrode assemblies A and B. The battery assembly is completed. The structural diagram is shown as follows Figure 5 shown.

[0141] Comparative Example 3 The preparation steps (1) to (4) are the same as those in Comparative Example 1.

[0142] (5) Assembly of electrode assembly A: Place electrode assembly A into the pit of the aluminum-plastic film formed by punching, with electrode assembly A in contact with and aligned with the left side of the pit of the aluminum-plastic film, cover with the other half of the aluminum-plastic film, and then press the side with electrode assembly A. Apply glue to the aluminum-plastic film corresponding to the right boundary of electrode assembly A, and press the upper and lower layers of aluminum-plastic film to solidify.

[0143] (6) Assembly of electrode assembly B: In the semi-finished product of step (5), electrode assembly B is placed in the vacant area on the right side of electrode assembly A, the left side of electrode assembly B is in contact with and aligned with the glue-coated area, and the entire aluminum-plastic film is packaged by top hot pressing. The top packaging is perpendicular to the glue-coated area, and the two intersect, and the contact position is sealed, so that electrode assemblies A and B are respectively in independent sealed cavities.

[0144] (7) Liquid injection packaging: The electrolyte is injected into the sealed cavities where the electrode assemblies A and B are located respectively, and the aluminum-plastic film at the liquid injection location is sealed by hot pressing, and all the tabs of the electrode assemblies A and B are led out of the aluminum-plastic film for subsequent processing.

[0145] (8) Series connection: The positive electrode tab of electrode assembly A and the negative electrode tab of electrode assembly B are connected together by laser welding to achieve series connection. The battery assembly is completed. The structural diagram is shown in the figure. Figure 6 shown.

[0146] Comparative Example 4 The preparation steps (1) to (4) are the same as those in Comparative Example 1.

[0147] (5) Electrode assembly assembly: Place the punched packaging film (aluminum-plastic film, thickness of about 90 μm) in the assembly fixture, with the pit facing upward, place electrode assembly A in the pit, and place electrode assembly B on top of electrode assembly A, and press tightly. Then, cover electrode assembly B with another piece of packaging film with the pit facing downward, and heat seal it around.

[0148] The rest is the same as Comparative Example 1.

[0149] Comparative Example 5 The preparation steps (1) to (3) are the same as those in Comparative Example 1.

[0150] (4) Liquid injection and packaging: All the electrode sheets and separators in the electrode assembly A and the electrode assembly B in comparative example 1 are stacked into an electrode assembly, which is then placed in an outer package, leaving a liquid injection port for packaging, and leading out a positive electrode tab and a negative electrode tab. After liquid injection, the liquid injection port is packaged to form a lithium-ion battery without series connection.

[0151] Comparative Example 6 The same as in Example 1 except that the thickness of the polymer seal area in the sealing area is 120 μm and the width of the sealing area is 2 mm.

[0152] Comparative Example 7 The same as in Example 1 except that the thickness of the polymer seal area in the sealing area is 16 μm and the width of the sealing area is 2 mm.

[0153] Comparative Example 8 Except that the thickness of the polymer seal area in the sealing area is 40 μm and the width of the sealing area is 5 mm, the rest is the same as in Example 1.

[0154] Comparative Example 9 In addition to the water permeability of the partition is 1.7×10 -2 g / (day·m 2 ·Pa) / 3mm, the rest is the same as that of Example 1.

[0155] The data and test results of each embodiment and comparative example are shown in Table 1.

[0156] Table 1

[0157] NG: 1. The target voltage platform cannot be reached and measurement cannot be performed. 2. The finishing materials of electrode assembly A and electrode assembly B refer to the materials of electrode assembly A and electrode assembly B that are in contact with the separator.

[0158] It can be seen from the above embodiments that the output voltage of the battery is increased by series connection according to the present application, and a high energy density and a high nail penetration rate are maintained, and the self-discharge rate is low. By adopting the separator of the present application, the stability in a humid environment is significantly improved, and the battery of the present application maintains a low thickness growth rate, indicating that the battery in the embodiment of the present application can prevent water vapor from penetrating into the battery, and improve the service life of the battery. When the water vapor permeability of the separator is too high, for example, exceeding the scope of the present application, the thickness growth rate of the battery is significantly increased, indicating that the water resistance of the battery is reduced, which may affect the service life. When the water vapor permeability of the separator is required to be too low, the requirements for the material are significantly increased, which will lead to a significant increase in manufacturing costs. When the ratio of the seal thickness to the seal width is lower than the lower limit of the scope of the present application, for example, the battery seal width is too large, although the packaging strength is improved, it will significantly reduce the energy density of the battery, and when the battery package thickness is too small, it will cause the packaging strength to be significantly reduced. When the ratio of the seal thickness to the seal width is higher than the upper limit of the scope of the present application, for example, when the package thickness is too large, the growth rate of the battery is significantly increased. Without being limited to any theory, the applicant believes that if the package thickness is too large, water vapor may penetrate from the package area into the battery, thereby reducing the water resistance of the battery.

[0159] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An electrochemical device, comprising a separator, the separator being sealed and connected to an outer package, forming independent cavities on both sides of the separator, each cavity encapsulating an electrode assembly and an electrolyte, the electrode assemblies in adjacent cavities being connected in series through tabs, and the separator comprising an ion insulating layer; The seal thickness T and seal width W of the partition and the outer package satisfy 0.01≤T / W≤0.05, and the seal width W is 1 mm to 7 mm; The separator further comprises a packaging layer, which is arranged on the edges of the ion insulating layer or on the entire surface thereof, and the melting point of the material of the packaging layer is 120 to 160°C.

2. The electrochemical device according to claim 1, wherein: The material of the ion insulating layer includes at least one of a polymer material, a metal material and a carbon material.

3. The electrochemical device according to claim 2, wherein the polymer material comprises at least one of polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyetheretherketone, polyimide, polyamide, polyethylene glycol, polyamideimide, polycarbonate, cyclic polyolefin, polyphenylene sulfide, polyvinyl acetate, polytetrafluoroethylene, polymethylenenaphthalene, polyvinylidene fluoride, polyethylene naphthalate, polypropylene carbonate, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-co-chlorotrifluoroethylene), silicone, vinylon, polypropylene, anhydride-modified polypropylene, polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, ethylene-acrylic acid copolymer, ethylene-vinyl alcohol copolymer, polyvinyl chloride, polystyrene, polyether nitrile, polyurethane, polyphenylene ether, polyester, polysulfone, amorphous α-olefin copolymer and derivatives thereof; The metal material includes stainless steel, or the metal material includes at least one of Ni, Ti, Cu, Ag, Au, Pt, Fe, Co, Cr, W, Mo, Al, Mg, K, Na, Ca, Sr, Ba, Si, Ge, Sb, Pb, In, Zn, and a combination or alloy thereof; The carbon material includes at least one of carbon felt, carbon film, carbon black, acetylene black, fullerene, conductive graphite film or graphene film.

4. The electrochemical device according to claim 1, wherein The encapsulation layer includes at least one of polypropylene, anhydride-modified polypropylene, polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, ethylene-acrylic acid copolymer, ethylene-vinyl alcohol copolymer, polyvinyl chloride, polystyrene, polyether nitrile, polyurethane, polyamide, polyester, amorphous α-olefin copolymer and its derivatives.

5. The electrochemical device according to claim 1, wherein The separator has a thickness of 6 to 100 μm.

6. The electrochemical device according to claim 1, wherein The ion insulating layer is a single layer or multi-layer structure.

7. The electrochemical device according to claim 1, having at least one of the following features: (a) The water permeability of the partition is less than or equal to 10 -3 g / (day·m 2 ·Pa) / 3mm; (b) the separator has a thickness of 10 to 40 μm; (c) The melting point of the material of the ion insulating layer is ≥ 165°C.

8. The electrochemical device according to claim 1, wherein The structure of the electrode assembly includes a winding structure or a stacked structure.

9. An electronic device comprising the electrochemical device according to any one of claims 1 to 8.